PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN REALISTIC MATHEMATICS EDUCATION (RME) PADA SISWA KELAS IV SEMESTER GENAP DI GUGUS V TAHUN PELAJARAN 2022/2023 - Rofek, Aenor; Dewi, Ratih Kesuma; Husein, Ach. Munawi; Hamidiah, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The study conducted in grade V students, in districts Panarukan, at SDN 1 and SDN 2 Alasmalang, Situbondo. The study aimed to determine differences in learning outcomes of students who are given treatment using Realistic Mathematics Education approach and students who provide treatment using lecture teaching methods in mathematics. The researchers examined the results of the evaluation of the two classes using the Mann Whitney test and it can be seen that the learning outcomes of the two-class research is not the same, or in other words there is a difference in student learning outcomes between the use of learning approaches RME and lectures on subjects fourth grade math digugus V District Panarukan. On average test results of the evaluation, the researcher found the average yield control class (Lecture) 88.50 and an average yield of experimental classes (RME) 95.83. It can be concluded that the results of experimental class learning using learning approach Realistic Mathematics Education is better than the control class learning outcomes teaching methods lectures.